Nutritional Quality Of Fermented Oil Palm Press Fiber By Local Microorganism - Anton Wicaksono; Yunilas; T H Wahyuni (Talenta Publisher, 2020)
Oil palm press fiber is a by product of the agro industry that has a low nutrient content. Nutrients of oil palm press fiber can be improved by fermentation using local microorganisms. The research was conducted experimentally using a completely randomized design (CRD) factorial pattern with 2 factors (3 x 3), namely first factor such as dose of local microorganisms (D1 = 1%, D2 = 3% and D3 = 5%) and second factor such as long of fermentation (L1 = 7 days, L2 = 14 days and L3 = 21 days), with 3 replications. The parameters measured were the nutritional content of fermented oil palm press fiber such as moisture, dry matter, crude protein, crude fat, crude fiber, ash, and nitrogen free extract (NFE). Based on the research results obtained a combination of 5% dose of local microorganisms and 14 days of fermentation time had a significant effect (P<0.05) to increased crude protein content but did not have a significant effect (P>0.05) on increased dry matter and nitrogen free extract (NFE) and decreased moisture content, crude fiber, and ash.